An impedimetric biosensor to test neat serum for dengue diagnosis - Cecchetto, Juliana [UNESP]; Carvalho, Fernanda C. [UNESP]; Santos, Adriano [UNESP]; Fernandes, Flavio C. B. [UNESP]; Bueno, Paulo R. [UNESP] (Elsevier B.V., 2015)
NS1, a non-structural dengue protein, has been used as a biomarker for the detection of viremia in dengue diagnosis. In this work, an impedimetric label-free immunosensor based on an anti-NS1 modified gold electrode was developed. To immobilize anti-NS1, a mixed self-assembled monolayer consisting of 11-mercaptoundecanoic acid (for covalent anti-NS1 attachment) and 6-mercaptohexanol (as a spacer) was prepared. The impedance spectra were recorded in the presence of a redox probe ( [Fe(CN)(6)](3-/4-)) to monitor changes in charge-transfer resistance associated with target binding both in PBS and neat serum. A calibration curve was constructed in order to obtain analytical parameters. NS1 was diluted in PBS to final concentrations in the linear range of 0.01-2.00 mu g mL(-1) with a sensitivity of 14.1 percentage decade(-1) (R similar to 0.99) and a limit of detection (LOD) of 3 ng mL(-1). A linear range 0.01-1.00 mu g mL(-1) of NS1 diluted in neat serum was also obtained (R similar to 0.98) with a sensitivity of 10.4 percentage decade(-1) and a LOD of 30 ng mL(-1). The results open new insights into the potential use of this biosensor for point-of-care and bedside applications for dengue diagnosis.
Keywords: Dengue; NS1 protein; Electrochemical impedance spectroscopy (EIS); Label-free biosensor; Blood serum